PENGARUH TERPAAN KONTEN DEWASA PADA MEDIA SOSIAL TIKTOK TERHADAP PERILAKU MENYIMPANG SEKSUAL REMAJA - Paulus Chaniago Thrystian (2023)
Tiktok application has become one of the most popular applications throughout the world. TikTok as a social media not only has a positive impact but also a negative impact on TikTok users themselves. The aim of this research is to determine the influence of exposure to adult content on TikTok social media on adolescent sexual deviant behavior. The theory used in this research uses social cognitive theory with quantitative research methods using explanatory methods. The population in this study were users of the TikTok application with a total sample of 400 respondents using a purposive sampling technique. The results of the study concluded that there was an influence of news exposure on deviant behavior with a large influence of 74.9% and the remaining 25.1% was influenced by variables outside of the research variables.